Ultrasonic transformation of micelle structures: Effect of frequency and power - Yusof, N.S.M.; Ashokkumar, M. (Elsevier, 2015)
A comprehensive investigation on the effect of ultrasonic frequency and power on the structural transformation of CTABr/NaSal micelles has been carried out. Sonication of this micelle system at various ultrasonic frequencies and power resulted in the formation and separation of two types of micelles. High viscoelastic threadlike micelles of ∼2 nm in diameter and several μm in length and tubular micelles possessing a viscosity slightly above that of water with ∼30-50 nm diameter and few hundred nm length. The structural transformation of micelles was induced by the shear forces generated during acoustic cavitation. At a fixed acoustic power of 40 W, the structural transformation was found to decrease from 211 to 647 kHz frequency due to the decreasing shear forces generated, as evidenced by rheological measurements and cryo-TEM images. At 355 kHz, an increase in the structural transformation was observed with an increase in acoustic power. These findings provide a knowledge base that could be useful for the manipulation of viscosity of micelles that may have applications in oil industry.